2016
DOI: 10.1016/j.fuel.2016.01.082
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and comparison of bio-oils obtained by hydrothermal liquefaction and fast pyrolysis of beech wood

Abstract: International audienceThere are many different ways to convert biomass into liquid fuels, mostly referred to as bio-oils. This paper presents the analysis of bio-oils produced by hydrothermal liquefaction and fast pyrolysis of beech wood. Both processes have a wide panel of parameters that can be optimised influencing the oil quality. Results of the analysis show that both oils have high acidities. Iodine values indicate a high degree of unsaturations. These two qualities seem to be inversely proportional in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(62 citation statements)
references
References 39 publications
7
52
0
Order By: Relevance
“…Starting as early as the 1970s but increasing significantly over the past decade, research groups at universities and national laboratories around the world have been investigating HTL of a variety of biomass feed types, such as woody biomass (Schaleger et al, 1982;Haarlemmer et al, 2016;Tran et al, 2017), plant biomass (Zhang et al, 2013;Zhu et al, 2015;Yan et al, 2016), food processing waste (Minowa et al, 1995;Yang et al, 2016;Posmanik et al, 2017), agricultural waste (Chan et al, 2014;Singh et al, 2015;Zhu et al, 2017), animal manure (Xiu et al, 2010;Theegala and Midgett, 2012), pulp/paper sludge (Xu and Lancaster, 2008), and algae Neveux et al, 2014;Faeth et al, 2016). Previous work in CHG over the same period has looked at conversion of agricultural waste (Pei et al, 2009) and industrial wastewater (Seif et al, 2016) to hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…Starting as early as the 1970s but increasing significantly over the past decade, research groups at universities and national laboratories around the world have been investigating HTL of a variety of biomass feed types, such as woody biomass (Schaleger et al, 1982;Haarlemmer et al, 2016;Tran et al, 2017), plant biomass (Zhang et al, 2013;Zhu et al, 2015;Yan et al, 2016), food processing waste (Minowa et al, 1995;Yang et al, 2016;Posmanik et al, 2017), agricultural waste (Chan et al, 2014;Singh et al, 2015;Zhu et al, 2017), animal manure (Xiu et al, 2010;Theegala and Midgett, 2012), pulp/paper sludge (Xu and Lancaster, 2008), and algae Neveux et al, 2014;Faeth et al, 2016). Previous work in CHG over the same period has looked at conversion of agricultural waste (Pei et al, 2009) and industrial wastewater (Seif et al, 2016) to hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…The HTL process occurs in subcritical water conditions (below 374°C and 22 MPa) (26). Mainly, the operating conditions for the biomass HTL process are 250°C -350°C and 8 -22 MPa (27)(28)(29)(30). Hydrothermal carbonization occurs at a lower temperature (180°C -250°C) and hydrothermal gasification in supercritical conditions of water, which both were not the aim of this study (31).…”
Section: Experimental Methodsmentioning
confidence: 97%
“…In practice, hydrothermal liquefaction is valued because it provides rapid conversion of waste biomass into bio-oil, avoiding the high energy cost of drying [42]. Most studies have shown that temperatures between 250 and 370°C are optimal for the production of bio-oil, with no general conclusion given about the effects of reaction time and moisture content [43]. Hydrothermal co-liquefaction is an interesting pathway and should be explored in future studies [44,45].…”
Section: Hydrothermal Liquefaction (Thermal Depolymerization)mentioning
confidence: 99%